2010
DOI: 10.1371/journal.pone.0015638
|View full text |Cite
|
Sign up to set email alerts
|

Tempo Rubato : Animacy Speeds Up Time in the Brain

Abstract: BackgroundHow do we estimate time when watching an action? The idea that events are timed by a centralized clock has recently been called into question in favour of distributed, specialized mechanisms. Here we provide evidence for a critical specialization: animate and inanimate events are separately timed by humans.Methodology/Principal FindingsIn different experiments, observers were asked to intercept a moving target or to discriminate the duration of a stationary flash while viewing different scenes. Time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
5
22
1
Order By: Relevance
“…In all cases, the background characters and their movements were totally unrelated to the foreground target and to the viewer's action. Carrozzo et al (2010) found that, for both the motor interception and the time discrimination task, the time estimates were systematically shorter in the sessions involving human characters moving in the background than in those involving inanimate moving characters. The presence of a systematic offset between the time estimates associated with biological movements and the time estimates associated with nonbiological movements is compatible with the hypothesis that there exist timing mechanisms differentially tuned to biological movements and to non-biological movements.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In all cases, the background characters and their movements were totally unrelated to the foreground target and to the viewer's action. Carrozzo et al (2010) found that, for both the motor interception and the time discrimination task, the time estimates were systematically shorter in the sessions involving human characters moving in the background than in those involving inanimate moving characters. The presence of a systematic offset between the time estimates associated with biological movements and the time estimates associated with nonbiological movements is compatible with the hypothesis that there exist timing mechanisms differentially tuned to biological movements and to non-biological movements.…”
Section: Introductionmentioning
confidence: 91%
“…Consistent with this hypothesis, there is recent evidence that time perception and motor timing are influenced by animacy: The observation of a biological movement performed by other people may bias the timing of a motor act or the judgement of perceived duration of an event (Watanabe 2008;Bove et al 2009;Carrozzo et al 2010;Zago et al 2011b;Mouta et al 2012;Wang and Jiang 2012). In particular, Carrozzo et al (2010) investigated two different timing tasks: (1) button-press responses aimed at intercepting a falling ball and (2) discrimination of the duration of a stationary flash.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations